Preamplifier design and analysis for dual output silicon photomultiplier - LONG Yuan; HUANG Yuefeng; HOU Huiliang; CHEN Yongzhong (He jishu)
BackgroundIn order to apply in different scenarios of silicon photomultiplier (SiPM) coupled scintillator detector, preamplifiers need to fulfill different requirements.PurposeThis study aims to design high-bandwidth, low-noise preamplifiers to adapt for different output modes of SiPM-coupled scintillator detector.MethodsBased on OPA855 chip and consideration of bandwidth and noise, a transimpedance amplifier (TIA) and a voltage feedback amplifier (VFB) were designed. The amplifier circuits were simulated and analyzed using PSpice for TI software to obtain circuit parameters. Then, the signal response and noise baseline level were measured and analyzed by experimental test using 241Am radioactive source and a sSiPM-coupled Cerium-doped Gadolinium Aluminum Gallium Garnet (GAGG(Ce)) detector.ResultsExperimental results show that these preamplifiers have good gain stability, high-bandwidth and low-noise. TIA's bandwidth is 101 MHz, lower than VFB's 381 MHz, but its baseline noise level (σnoise≈448.32 μV) is better than that of the VFB's ( σnoise≈680.96 μV).ConclusionsFor GAGG(Ce) detector ,both VFB and TIA meet the bandwidth design requirements of 2 ns for fast output pulse and 20 ns for standard output pulse, respectively. Limited by the inherent noise of circuits and the input capacitance of SiPM,TIA is suitable for energy measurements and small-area SiPM applications, while VFB is more suitable for time measurements and large-area SiPM arrays.